SoIve the system of equations by elimination. (Addition)
1)-2x + 4y = -22
2x + 8y = –26
2 answers:
Answer:
(3, - 4 )
Step-by-step explanation:
Given the 2 equations
- 2x + 4y = - 22 → (1)
2x + 8y = - 26 → (2)
Adding the 2 equations term by term will eliminate the x- term, that is
12y = - 48 ( divide both sides by 12 )
y = - 4
Substitute y = - 4 into either of the 2 equations and solve for x
Substituting into (2)
2x + 8(- 4) = - 26
2x - 32 = - 26 ( add 32 to both sides )
2x = 6 ( divide both sides by 2 )
x = 3
solution is (3, - 4 )
Answee:
We have these two equations:
-2x +4y =-22
2x + 8y -26
We need to try to get the same number multiplying both x or y, I think we can make the 2 of the first equation negative, for that, we multiply all the equation by -1:
2x + 8y =-26 ---- -2x - 8y =26
Now we have this:
-2x +4y = -22
-2x -8y = 26
Now e substract both equations:
-2x - (-2x) +4y -(-8y) = -22-26
12y = -48
Y = -48/12 = -4
And we replace to get x
-2x + 4y = -22
-2x +4*(-4)=-22
-2x - 16 = -22
x= -6/-2 =3
You might be interested in
Answer:
that is false! im pretty sure!
let me know if u need any more help cutie!
Step-by-step explanation:
The answer is 277 for your question
Answer:
hen is in training of Marathon Vande hand run 8 Miles next day he plans to run the same I bless have much so how far does he planned
Step-by-step explanation:
the hendrun 8 and half miles the next radio Follow Me animal lover
Answer:
First, we bring the equation to the form ax²+bx+c=0, where a, b, and c are coefficients. Then, we plug these coefficients in the formula: (-b±√(b²-4ac))/(2a) . See examples of using the formula to solve a variety of equations.
F(x) -2 +6 = 4 The answer is 4